The use of social media by organisations when engaging with their online community: the collective storytelling phenomenon - Davids, Moegamat (Department of Information Systems, 2018)
The pervasive nature and use of social media has transformed society and this transformation has attracted significant attention from both industry and academia. The organisational implementation and use of social media are plagued with many challenges, leaving managers frustrated at not achieving the desired results. This emergent and complex nature of the social media phenomenon requires researchers to consider novel approaches when conducting social media research. As the number of Information Systems (IS) researchers conducting research on the social media phenomenon increases, so too does the need to develop relevant and rigorous social media theories. This challenge must be addressed by IS researchers who are contemplating, or are busy conducting research on the social media phenomenon. My PhD thesis responds to the call made by academics and practice for the development of relevant and rigorous social media theories, with the aim of providing a better explanation than what is currently found in the social media literature on social media use within an organisational context. Owing to the emergent nature of the social media phenomenon, the grounded theory method (GTM) is used to develop a substantive theory that increases understanding of this particular phenomenon. Two organisations are selected as the case studies. Both are industry leaders in South Africa, with one being a prominent retailer with a very visible social media presence and the other, being a leading university in South Africa, which is actively growing its social media presence. The results show that organisations enter into a collective storytelling process with their online community. Risk to reputation and the need for online community engagement are identified as reasons for this. Organisations using social media need to be aware of the following conditions that impact on social media use: (1) the social media landscape, (2) the characteristics of social media for use, (3) the relationship between content and social media, (4) content quality, (5) the online community-organisation power dynamic, and (6) the provision of a seamless online experience for the community. Challenges during the collective storytelling process lead to organisations experiencing social media use failures. To overcome these failures, organisations implement education interventions. An evolving supportive social media strategy that provides formal guidelines for social media use ultimately leads to a reduction in the organisational risk to reputation and an improvement in online community engagement, initially identified as the reasons why organisations decide to use social media. The main theoretical contribution is the development of a holistic theoretical framework using the GTM to better explain social media use within organisations when engaging with their online community.